1994
DOI: 10.1177/001872089403600102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging, Skill Modification, and Demand Alternation on Multiple- Task Performance

Abstract: The magnitude of age effects in single- and dual-tasks may be affected by the degree to which performance depends on well-learned skills that were previously developed. In addition, age-effects may be affected by the requirement to modify these skills and by attentional requirements emerging from the mutual relation of subtasks. Effects of skill modification and emergent attentional processes were examined in an experiment in which experienced subjects performed two perceptual-motor tasks, a vehicle steering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…For example, when drivers switch from regular to anti-lock brakes they often go through a difficult transition period where they Driving and attention 401 continue to pump their brakes when they try to stop suddenly. Similarly, Korteling (1994) demonstrated that steering and using the accelerator were automatic in experienced drivers by trying to get them to reverse the polarity of their actions (i.e. turn the wheel right when they wanted to go left, and hit the gas when they wanted to slow down).…”
Section: Driving and Attention 399mentioning
confidence: 99%
“…For example, when drivers switch from regular to anti-lock brakes they often go through a difficult transition period where they Driving and attention 401 continue to pump their brakes when they try to stop suddenly. Similarly, Korteling (1994) demonstrated that steering and using the accelerator were automatic in experienced drivers by trying to get them to reverse the polarity of their actions (i.e. turn the wheel right when they wanted to go left, and hit the gas when they wanted to slow down).…”
Section: Driving and Attention 399mentioning
confidence: 99%
“…Decline in cognitive and physical abilities, reduced memory and visual perceptual skills , impairment in acuity and visual field (McGwin et al, 2000), and difficulty in processing traffic stimuli , are associated with an increased risk of accidents (Parasuraman and Nestor, 1991;Drachman and Swearer, 1993;Parasuraman and Nestor, 1993;Korteling, 1994;Mendez et al, 1997;Bedard et al, 1998;Duchek et al, 1998;Rizzo et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…This may be especially difficult for older pedestrians, given the evidence demonstrating age-related changes in performance in these areas (Corso, 1981;Korteling, 1994;McDowd and Shaw, 2000;Roeneker et al, 2003;Salthouse, 1991). Non-optimal road-crossing behaviour may then, in part, explain the high rate of fatal and serious injury crashes found for older pedestrians (Australian Transport Safety Some studies point to a link between age-related declines in driving and road-crossing skill and increased crash risk (Carthy et al, 1995;Helmers et al, 2004;Mathey, 1983;Oxley et al, 1997a;Oxley, 2000), and suggest that this may, in part, be caused by increasing difficulties in judging safe gaps in the traffic especially under complex conditions, such as two-directional traffic or when a decision needs to be made quickly.…”
Section: Introductionmentioning
confidence: 99%